Pornografi dan Pornoaksi Dalam Perspektif Al-Qur'an - Chirzin, Muhammad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
Porn or pornography is a treatment of obscene subjects in writing, pictures, mails, etc. Nowadays pornography and porno action have spread throughout the country and caused many moral and familial problems, such as illicit sexuality, infidelity and rape. With regard to porn issues, Qur'anic verses say to the believing men and women that they should lower their gaze and guard their modesty, that they should not display their beauty and ornaments except what ordinarily appear thereof. The believing women should draw their veils over their bosoms and not display their beauty except to their husbands, their fathers or young children who have no attraction of sexual engagement. The rule of modesty applies to men as well as women. A brazen stare by a man at a woman is a breach of refined manners. Where sexual engagement is concerned modesty is not only a good concept of expression, but also in creating balance between protecting the weaker sex and guarding the spirit of the stronger sex. Modesty is equally important for both men and women. Nevertheless the scripture requires that women should be given a greater amount of privacy, especially in terms of dress code, i.e. covering the bosom, than men on the account of sexual specificity and social context.